The important role of the DTPB in the development of Islamic P2P lending in Indonesia - Rofiqo, Azidni; Zamarkasi, Ainul; Bin Abd Razak, Abdurrizqi (Faculty of Business & Economics, Universitas Islam Indonesia, 2023)
Purpose − the purpose of this study is the determinants of factors influencing to the intention in Islamic Peer to Peer (P2P) financing platform. Methodology − Quantitateve approach with distributing questionnare accross Islamic P2P financing platforms consisting of ethis.co.id, ammana.id, alamisharia.id, danasyariah.id and qazwa.id employed. 121 usable sample is analsyed with using PLS-SEM and Smart PLS 3.2 opreated as analysis tools.Findings − The results show that normative influence affects positively and significantly the subjective norm. In terms of attitude control, only perceived uselfulness has insiginificant influence on attitude. Moreover, self-efficacy and facilitating condition has a positive and significant impact on perceived behaviour control. Attitude and perceived berhaviour control affect intention to participate. However, subjective norm has insignificant impact on intention to participate in P2P financing platform.Implications − The study suggests that islamic P2P should focus on relative advantage and perceived ease of use, perceived behavioral control in order to maintain their customers.Originality − Decomposed Theory of Planned Behavior model (DTPB) used in the study as the first study in Islamic P2P lending in Indonesia